Šolska ocena - Marjanovič Umek, Ljubica (Psihološka obzorja (Ljubljana), 2006)
Our paper presents results of a research of factors of the academic achievement of the ninth-grade elementary school students. Four hundred twenty-seven adolescents participated, among them 225 girls and 202 boys. We attempted to determine the extent in which the academic achievement (evaluated by means of national examinations and teachers' marks) in Slovene, mathematics and biology can be predicted by students' individual characteristics (language competence, intellectual abilities and personality dimensions) and some variables related to the family environment (parents' educational level, parental pressure on adolescent's learning, number of books at home, parents' wishes concerning the continuation of adolescent's education). By means of hierarchical linear modeling (HLM) we found rather small across-schools differences in average students' achievement; the proportion of the school-level variance ranged between 0% and 9%. On the otherhand, variation between students within schools was larger; the proportion of the student-level variance in achievement ranged between 91% and 100%. The variables related to the student and the family environment explained between 37% and 63% of the variance in achievement evaluated by means of national examinations, and between 56% and 62% of the variance in achievement evaluated by means of teachers' marks, respectively. The most important predictors of the achievement were language competence, intellectualabilities, personality dimensions conscientiousness and openness/intellect, two components of parental influence to the school work, namely parental pressure and help with the school work, and the parents' educational level. We further tried to determine the extent in which schools differ with regard to the evaluated individual characteristics of adolescents and to the family environment variables. We found out that the across-school variation of adolescents' intellectual abilities, parents' educational level and certain components of parental influence on the student's school work is larger than the across-school variation of students' achievement, with the exception of the national examination in biology.
Keywords: učna uspešnost; preizkusi znanja; govor; intelektualne sposobnosti; osebnost; personality; družinsko okolje